Human natural killer (NK) cell activation by luteolin from Brucea javanica leaves - Ismail, Norzila; Abdullah, Hasmah; Seidel, Veronique; Rotondo, Dino (Academic Journals, 2018)
There is growing interest in using natural substances from plants to potentially enhance anticancer activity. A key target in this respect is natural killer (NK) cells in order to generate an anticancerimmune response. Luteolin used in this study was derived from a local plant Brucea javanica leaves extract; through a bioassay-guided fractionation. The expression of interleukin-2 (IL-2) and interferon-γ (IFN-γ) was increased after 20 h treatment of 0.1 µM luteolin in human mixed lymphocytes, which reflects the activation of NK cells. This was further confirmed in co-culture experiments. NK cellinduced K562 target cell death was increased in the presence of luteolin. These results show that luteolin activates NK cells to kill target cells indicating the potential use of luteolin as an anticancer immunostimulant.